Influence of molecular rebinding on the reaction rate of complex formation. Issue 35 (1st September 2021) - Kalwarczyk, Tomasz; Bielec, Krzysztof; Burdzy, Krzysztof; Holyst, Robert
Abstract : The encounter-full complex transition depends on the number of rebinding given as the reactant's radii to the separation distance ratio. Abstract : We simulated Brownian diffusion and reaction–diffusion processes to study the influence of molecular rebinding on the reaction rates of bimolecular reactions. We found that the number of rebinding events, N reb, is proportional to the target's size and inversely proportional to the diffusion coefficient D and simulation time-step Δ t . We found the proportionality constant close to π −1/2 . We confirmed that N reb is defined as a ratio of the activation-limited rate constant k a to the diffusion-limited rate constant, k D . We provide the formula describing the reactivity coefficient κ, modelling the transient-native complex transition for the activation-controlled reaction rates. We show that κ is proportional to ( D /Δ t ) 1/2 . Finally, we apply our rebinding-including reaction rate model to the real reactions of photoacid dissociation and protein association. Based on literature data for both types of reactions, we found the Δ t time-scale. We show that for the photodissociation of a proton, the Δ t is equal to 171 ± 18 fs and the average number of rebinding events is approximately equal to 40. For proteins, Δ t is of the order of 100 ps with around 20 rebinding events. In both cases the timescale is similar to the timescale of fluctuation of the solvent molecules surrounding the reactants; vibrations and bending in the case of photoacid dissociation and diffusional motion for proteins.